Journey through the bible lands (London : International Video Network, 1989)
Watch the bible come to life in this video tour of the holy land. Begin your visit at the Red Sea, following the path of Moses and the Israelites through the desert of Sinai. Continue into the Negev, past the ancient walls of Hebron, to Bethlehem, where Jesus was born
Copy available in DVD format
Title from data sheet
Keywords: Palestine -- Description and travel